Structure of tri-n-butyltin hydroxyacetate - Chalupa, Jan; Padělková, Zdeňka; Růžička, Aleš (Univerzita Pardubice, 2009)
The structure of tri-n-butyltin derivative of hydroxyacetic acid was prepared and structurally characterized by X-ray crystallographic techniques in the solid state. This compound reveals linear polymeric structural character with five-coordinated tin atoms. Coordination geometry of tin atoms is trigonal bipyramidal with all three carbon atoms in equatorial positions, monodentatelly bonded carboxylic oxygen and the hydroxo oxygen atom from the adjacent molecule in the axial positions forming thus the linear chain. Two independent molecules/chains are nearly perpendicularly oriented and interconnected by H-bonding by OH group from one chain to uncoordinated oxygen of carboxylic group of second chain in the crystal lattice.